PELAKSANAAN KONTRAK UNIT PRICE ANTARA KONTRAKTOR DENGAN DINAS PEKERJAAN UMUM KABUPATEN SOLOK SELATAN (Studi Kasus Pembangunan Baru Jembatan Kabupaten Oleh CV. Mitreka) - , Suci Astri Hastuti, Dwi Haryati, S.H., M.H. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Research about âImplementation contract of unit price between contractors with government service for public works of South Solok districtâ, this research aims to know the implementation contract of unit price between contractors with Government Service for Public Works of South Solok district and the result of law if inappropriate with the contract and to know the resolving of implementation contract of unit price between contractors with Government Service for Public Works of South Solok that inappropriate with the content of the contract (default). Research was implemented by using juridical empirical approach or nondoctrina (socio-legal research) is type of research to behave the law that was focused on sociological perspective. This research was using qualitative research method. Collecting primary data technique was implemented by instrument forms interview guidelines. To complete the data was also conducted literature research by documentation study to obtain the secondary data. Implementation of contract construction of unit price consists of some phases that are pre-contract, making contract, and post-contract. Pre-contract including supplying planning, establishing auction committee, pre-qualification of company, structuring auction documents, auction announcement, document annexation, pricing, explanation of auction, delivering and opening offering, evaluation of offering, announcement of the candidate of winner, protest, pointing to the winner, and then making contract phase that is contract of unit price that emphasizing to the procedure of payment that based on measuring together over of volume works that based on unit price determined by committee of supplying goods and service in order to district building of South Solok district. And then post-contract phase is after the contract has end to be made and signed by both of the parties and moreover the contractor executor starting implementation of those government project. Work contract unit price agreed upon by both parties is not goes according to the contract, where the service providers do defaults of leaving unfinished work carried out which resulted in the termination of the service users make a contract.